2000
DOI: 10.1046/j.1469-8137.2000.00664.x
|View full text |Cite
|
Sign up to set email alerts
|

Maternal transmission of adaptive modifications in salt‐treated Sorghum bicolor: a first stage in ecotypic differentiation?

Abstract: Following a 3-wk pretreatment with 150 mM NaCl, Sorghum plants were able to survive exposure to 300 mM NaCl, a lethal concentration for nonpretreated plants. This response is termed salt adaptation. Although the population was initially homogeneous, Na-includer and Na-excluder individuals coexisted after the achievement of the salt-adaptation response, and a large diversity in size of the seeds produced was observed at the end of the life cycle. Offspring of salt-adapted plants were exposed to a new sal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2001
2001
2011
2011

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 51 publications
1
7
0
Order By: Relevance
“…2). This increase in variability was previously noticed and interpreted as resulting from differentiation of two modes of osmoregulation (Na-excluder and Na-includer) within an initially homogeneous population (Amzallag, 1999 a [4] , 2000 a [6] ). Accordingly, the individuals sampled here at the second and the third period have been separated in two sub-populations.…”
Section: Relationship Between Shoot Dw and Shoot Na + Contentsupporting
confidence: 65%
See 1 more Smart Citation
“…2). This increase in variability was previously noticed and interpreted as resulting from differentiation of two modes of osmoregulation (Na-excluder and Na-includer) within an initially homogeneous population (Amzallag, 1999 a [4] , 2000 a [6] ). Accordingly, the individuals sampled here at the second and the third period have been separated in two sub-populations.…”
Section: Relationship Between Shoot Dw and Shoot Na + Contentsupporting
confidence: 65%
“…This phenomenon was characterized by emergence of two distinct modes of osmoregulation, Na-excluder and Naincluder, within the initially homogeneous population (Amzallag, 1999 a [4] ). Rather than being caused by genetic heterogeneity (Amzallag, 2000 a [6] ), variability in osmoregulation is related to enhanced sensitivity to microenvironmental variations during initiation of the adaptation response (Amzallag, 1999 a [4] ). Accordingly, it seems that the mode of osmoregulation emerging through maturation of salt adaptation is conditioned by self-organization processes, and that two discrete ªattractorsº (reaching towards the Na-excluder and Na-includer modes) condition the newly-emerging regulation pathway (Amzallag, 1999 a [4] ).…”
Section: Introductionmentioning
confidence: 99%
“…In many cases, the physiological adaptation to environmental modifications is revealed by an increase in tolerance rather than a recovery of the initial rate of growth Amzallag 1999aAmzallag ,1999b. In S. bicolor exposed to salinity, it was observed that optimality (measured by developmental or physiological parameters) is even modified towards the new saline conditions as a consequence of physiological adaptation (Amzallag, Seligmann & Lerner 1997;Amzallag 2000). These examples show that the estimation of stress from measurements of growth is not only imprecise, but also frequently incorrect.…”
Section: Towards a New Definition Of Optimalitymentioning
confidence: 99%
“…Such a rapid transformation of so many characteristics would imply a very weak stability for the species! It does not mean that in some rare cases acquired characteristics also play a role 4 . Of course such a rare phenomenon does not shake neo‐Darwinism fundamentally.…”
Section: Discussionmentioning
confidence: 98%
“…It does not mean that in some rare cases acquired characteristics also play a role. 4 Of course such a rare phenomenon does not shake neo-Darwinism fundamentally.…”
Section: Discussionmentioning
confidence: 99%